TRANSFORMASI PELAYANAN PUBLIK DIGITAL DI MASA PANDEMI COVID-19 UNTUK MEWUJUDKAN E-GOVERNMENT DI LINGKUNGAN PEMERINTAH DAERAH KOTA JAMBI. - Hendriyaldi, Hendriyaldi; Erida, Erida; Yanti, Ovie (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The COVID-19 pandemic has also accelerated virtual transformation in various countries. Technological developments are increasingly sophisticated. Various innovations have sprung up in every government agency. This affects the accessibility of public services. This online service is the result of the implementation of E-Government. This study aims to determine the transformation of digital public services during the Covid-19 pandemic to realize E-Government within the Jambi City Regional Government. This study uses an observational research type. Forms of data collection with documents, observations and in-depth interviews then the researchers tested the credibility and carried out data analysis including data reduction, data presentation and research conclusions. The research design used is a qualitative research method. All data were obtained using analysis on various related literature. The results of the study show that if you want to realize the maximum e-government system in Jambi City, synergy is needed from various Regional Apparatus Organizations (OPD) related to data in the Jambi City Government. So that this digital government transformation is felt by the community, because if the government wants to rebuild public trust, then by increasing government transparency, accessibility, communication, and quality of service the community will feel directly.